2019
DOI: 10.15408/harkat.v15i1.13440
|View full text |Cite
|
Sign up to set email alerts
|

Landasan Agama Dalam Pendidikan Pubertas Di Sekolah Dasar

Abstract: Abstract. Indonesia is experiencing a demographic bonus, and a good education and health situation will determine the quality of human resources so that this situation does not turn into a demographic burden or disaster. The Indonesian Adolescent Reproductive Health Survey shows the in-depth knowledge of adolescents about puberty, whereas adolescence is a golden period that will determine the quality of the next generation. This study aims to get a picture of the perception of teachers and students in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…They are selective in choosing material to deliver in class therefore not all materials are covered. Study found that most of the teacher tend to give the responsibility to deliver the 'sensitive' topics to other teacher who in charge to religious subject [12]. The other study found that about 80% of puberty education needs to include understanding of 'skin health education' , 'nutrition education' , 'education about emotional change' , teaching methods of transmission and prevention of HIV and other sexually transmitted diseases, and 'training in the management of normal and painful menstruation and the cause [13].…”
Section: Knowledge Of Pubertymentioning
confidence: 98%
“…They are selective in choosing material to deliver in class therefore not all materials are covered. Study found that most of the teacher tend to give the responsibility to deliver the 'sensitive' topics to other teacher who in charge to religious subject [12]. The other study found that about 80% of puberty education needs to include understanding of 'skin health education' , 'nutrition education' , 'education about emotional change' , teaching methods of transmission and prevention of HIV and other sexually transmitted diseases, and 'training in the management of normal and painful menstruation and the cause [13].…”
Section: Knowledge Of Pubertymentioning
confidence: 98%
“…38 Tentunya tindakan free sex tidak bisa diterapkan di Indonesia, hal ini dikarenakan Indonesia masih sangat kental akan normal agama dan juga nilai susila dan agama. 39 Pemerintah melalui Badan Kependudukan Keluarga Berencana (BKKBN) dan Kementerian Kesehatan (Kemenkes) dalam mengantisipasi hal tersebut, menyelenggarakan sebuah program untuk anak muda, agar anak muda Indonesia mampu merencanakan masa depannya dengan mempromosikan Penundaan Usia Perkawinan (PUP) melalui kegiatan Pelayanan Kesehatan Perduli Remaja (PKPR) dengan mengusung remaja sebagai role model serta sebagai agen perubahan melalui kegiatan Generasi Berencana (Genre) melalui program Jurnal Kesehatan Reproduksi, 14(2), 2023 Pusat Informasi dan Konseling Remaja (PIK-R) yang di tempatkan di sekolah-sekolah. 40 Penelitian ini memiliki beberapa keterbatasan, yaitu: pertama dari sisi desain penelitian yang dipakai berupa cross sectional study yang memiliki kelemahan semua variabel di ukur dalam satu waktu tanpa melihat dampak pajanan terlilebih dahulu.…”
Section: Pembahasanunclassified
“…[29][30][31] Diperlukan upaya pendidikan sejak dini untuk mempersiapkan menghadapi pubertas sehingga remaja dan pelajar memiliki komitmen dan kompeten serta tanggung jawab atas kesehatan reproduksi dan seksualitasnya. 29,[32][33][34] Konsistensi penggunaan kondom dalam upaya pencegahan penularan HIV sangat dipengaruhi oleh pasangan seks selain faktor negosiasi hal ini dapat membantu untuk konsisten dalam menggunakan kondom. 29,35 Penggunaan kondom, akses memperoleh kondom dan juga keterjangkauan kondom dapat membantu populasi kunci untuk bisa konsisten dalam menggunakan kondom selain faktor negosiasi dengan pasangan dan juga faktor income yang diperoleh oleh LSL.…”
Section: Pendahuluanunclassified